Protein synthesis in rabbit reticulocytes: characteristics of the protein factor RF that reverses inhibition of protein synthesis in heme-deficient reticulocyte lysates. - Grace, M (1982)
During heme deficiency in reticulocyte lysates, the heme-regulated translational inhibitor of protein synthesis (HRI) is activated and shuts off protein synthesis. In partial reactions, HRI phosphorylates the Mr 38,000 subunit (alpha subunit) of eukaryotic initiation factor 2 (eIF-2), which forms a ternary complex, Met-tRNAf X eIF-2 X GTP. The eIF-2 alpha (P) thus formed is not recognized by two eIF-2 ancillary factors, Co-eIF-2B (which promotes the dissociation of the ternary complex at high Mg2+) and Co-eIF-2C (which reverses the inhibition of ternary complex formation), and thus, is presumably inactive in peptide chain initiation. A protein factor, designated RF, which reverses inhibition of protein synthesis in heme-deficient reticulocyte lysates, has been purified from reticulocyte cell supernatant. RF is a high molecular weight (Mr approximately equal to 450,000) protein complex composed of multiple polypeptides. An active RF preparation contains Co-eIF-2B and Co-eIF-2C activities, and these two activities in RF preparation are not inhibited by HRI and ATP--i.e., eIF-2 alpha (P) is recognized. During purification, RF remains associated with eIF-2 activity (eIF-2 X RF) and can be freed of this eIF-2 activity by CM-Sephadex chromatography. Both eIF-2 X RF and RF contain a Mr 38,000 polypeptide component that is indistinguishable from the Mr 38,000 subunit of eIF-2 by two-dimensional gel electrophoresis. It has been observed that a significant part of this Mr 38,000 polypeptide component in eIF-2 X RF and almost the entire Mr 38,000 polypeptide component in RF remain unphosphorylated after prolonged incubation with HRI and ATP. A possible role of this free Mr 38,000 polypeptide in RF action is discussed.